2019
DOI: 10.1371/journal.pone.0216712
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic, mitochondrial, renal and hepatic safety of enfuvirtide and raltegravir antiretroviral administration: Randomized crossover clinical trial in healthy volunteers

Abstract: Context Classical antiretroviral agents may acutely impact on metabolic, mitochondrial, renal and hepatic function in HIV-infected and uninfected persons. Fusion and integrase inhibitors are supposed to be safer, but have been scarcely investigated. To avoid any interference with HIV or other antiretrovirals, we assessed markers of these toxicities in healthy adult volunteers treated with Enfuvirtide (T20) or Raltegravir (RAL). Methods Twenty-six healthy participants were randomized to T20/90mg vs. placebo (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Furthermore, given the overwhelming use of combined therapy, it is difficult to critically assess the differential roles of ART regimens. This review highlights various mechanisms by which both HIV-encoded proteins and ART treatments damage critical mitochondrial functions; however, a multitude of other mechanisms have been studied but are not mentioned here for brevity [ 14 , 68 , 69 , 85 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, given the overwhelming use of combined therapy, it is difficult to critically assess the differential roles of ART regimens. This review highlights various mechanisms by which both HIV-encoded proteins and ART treatments damage critical mitochondrial functions; however, a multitude of other mechanisms have been studied but are not mentioned here for brevity [ 14 , 68 , 69 , 85 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the unique processes by which HIV-infection in combination with ART leads to mitochondrial dysfunction may allow for the development of improved therapeutics and quality of life for PLHIV. Considering the prevalence of the inclusion of NRTIs, NNRTIs, PIs, and INSTIs, as well as the evidence supporting increased adverse effects of these drugs compared to fusion inhibitors and coreceptor agonists, for the purposes of this review we hereafter focus on mitochondrial toxicity associated with NRTIs, NNRTIs, PIs, and INSTIs [ 107 , 108 ]. These results, along with mitochondrial deregulation by all ART classes, are summarized in Table 1 .…”
Section: Current Outlookmentioning
confidence: 99%
“…In our cohort, patients on a 2-drug regimen with 3TC-DTG show a lower rate of hepatic steatosis compared with those on other ARV regimens. The good tolerability of this strategy has already been described, with various real-life studies highlighting the favorable effects on total cholesterol and tryglicerides even in the short-term [22][23][24], The class of Integrase Inhibitors has shown since its introduction an overall better tolerability compared with boosted-Pis and NNRTIs [25,26] and this reflects also on mitochondrial toxicity and fasten lipids profile [27]. Most recent guidelines [28] have become aware of the importance of ARV regimens in preventing NAFLD and suggest the use of lipid-neutral ARV regimens in patients at risk of developing NAFLD.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, we are aware that assessing specific PBMC composition would be of interest to assess potential interference of cell populations in observed findings, as well as preventing platelet contamination (Tin et al, 2016;Sun et al, 2018). However, we should take into consideration that PBMCs have been demonstrated to be a reliable and non-invasive model to perform mitochondrial studies and that is the present gold standard for mitochondrial toxicity evaluation (Garrabou et al, 2009;Moren et al, 2015;Barroso et al, 2019). Additionally, the potential follow-up of patients for an extended period of time over PEP administration and additional measures for evaluation of mitochondrial toxicity or specific cell toxicity profiling may be of interest for further approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For mtDNA quantification, a fragment of the mitochondrial conserved gene mt12SrRNA and the nuclear constitutive gene nRNAseP were amplified simultaneously and in duplicate by multiplex quantitative Real-Time PCR. We used Applied Biosystems technology (CA, USA) in a 96-well plate and results were expressed in relative units as the ratio between mtDNA to nuclear DNA (mt12SrRNA/nRNaseP), as previously validated (Côté et al, 2011) and reported by our group (Moren et al, 2015;Catalán-García et al, 2016;Barroso et al, 2019) and other groups FIGURE 1 | Non significant differences in mtDNA content were observed within each therapeutic group intervention (before and after each treatment), but significant differences were found between the different PEP regimens (PI plus AZT + 3TC vs. PI plus TDF + FTC). Results were expressed as the ratio of mitochondrial 12SrRNA gene with respect to the constitutive nuclear RNAseP gene.…”
Section: Nucleic Acid Isolation From Pbmc and Quantification Of Mtdnamentioning
confidence: 99%